PENGARUH MOTIVASI DAN STRES KERJA TERHADAP KINERJA KARYAWAN PADA PT. NADYNE MEDIA TAMA JAKARTA SELATAN - Yanti, Citra Pebri; Priadi, Andri (Publika Citra Media, 2025)
The purpose of this study was to determine the effect of work motivation and job stress on employee performance. This study employed quantitative research, employing a saturated sampling technique with 54 employees. Data collection involved primary and secondary data. The author employed multiple linear regression analysis for data analysis. The results indicate that: 1) Partially, there is a positive and significant effect between motivation and employee performance at PT Nadyne Media Tama. 2) Partially, there is a negative and significant effect between work stress and employee performance at PT Nadyne Media Tama, South Jakarta. 3) Simultaneously, there is a positive and significant effect between work motivation and job stress on employee performance at PT Nadyne Media Tama, South Jakarta.